A Review of Current Evidence of Olmesartan Medoxomil Mimicking Symptoms of Celiac Disease. (April 2015) - Sanford, Michele L.; Nagel, Angela K.
Objective: To review the evidence of an association between olmesartan medoxomil and symptoms mimicking celiac disease. Data Sources: Literature was searched in PubMed (1965-November 2013) using the key words or MeSH terms olmesartan, enteropathy, celiac disease, sprue, and diarrhea. References from the Food and Drug Administration (FDA) and Dipiro's Pharmacotherapy eighth edition textbook were also reviewed. Data Synthesis: There have been recent implications of olmesartan medoxomil being linked to symptoms mimicking celiac disease. Investigators first identified the association in 22 patients who presented with presumed refractory celiac disease. Upon further evaluation, it was discovered that these symptoms improved when olmesartan was discontinued. In response to this report, additional case studies have been published. DeGaetani et al also further analyzed patients with seronegative villous atrophy from the Celiac Disease Center and found that olmesartan accounted for 22% of previously unclassified sprue cases. Conversely, the authors of the ROADMAP trial, which compared olmesartan to placebo, found no significant differences in the incidence of gastrointestinal adverse effects. Conclusions: There is growing evidence supporting the association between olmesartan and sprue-like symptoms; however, further research is warranted. These symptoms can be life threatening and clinicians should be aware of the potential association.